State change detection on PV panels based on image processing - Özbey, Nigar; Karaköse, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2015)
The shadow occurring in Photovoltaic (PV) panels is one of the important factors that effect the system's performance. In this work, the change detection algorithm is used to determine the shadow occurring on the PV panels. In order to make the change detection, first among the images of panel, an image in which there is not any shadow is determined to use as a reference, then the detection of the shadowy area in the instant image is made, and the coordinate information of the occurring shadow is acquired. The area which the shadow covers and the shadow proportion are calculated by using the coordinate information of the shadow on the panel because the area which the occurring shadow covers and the shadow proportion determine the performance of panel. The performance of algorithm and the occurring shadowy area on the panel are demonstrated through experimental results. © 2015 IEEE.
PV Panellerde Görüntü Işleme Tabanli Durum De?işikli?i Tespiti
2015 23rd Signal Processing and Communications Applications Conference, SIU 2015 -- 16 May 2015 through 19 May 2015 -- Malatya -- 113052
Keywords: Change Detection Algorithm; Connection Configuration; PV Arrays; Reconfiguration